A method for preparing a modified aluminum-based composite lithium adsorbent
By introducing hydrothermal reaction and lithium hydroxide soaking steps into the modified aluminum salt adsorbent and growing manganese-based ion sieve in situ, a modified aluminum-based composite lithium adsorbent with high adsorption capacity, good cycle stability and wide application range was prepared, and the shortcomings of existing adsorbents were solved.
Patent Information
- Application Number
- CN202410661233.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-27
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-05-27
AI Technical Summary
The existing modified aluminum salt adsorbents have problems such as insufficient adsorption capacity, low circulation stability and insufficient application range of brine in terms of lithium ion adsorption.
The aluminum-based adsorbent precursor is prepared by reacting soluble aluminum salt, lithium salt and urea in a hydrothermal reaction, and then soaking in a lithium hydroxide solution and adding manganese salt for hydrothermal reaction, and a manganese ion sieve is grown in situ to form a modified aluminum-based composite lithium adsorbent.
It improves adsorption capacity, enhances circulation stability, and expands the scope of application of lithium ions in brine.
Smart Images

Figure BDA0004859692850000041 
Figure BDA0004859692850000042 
Figure HDA0004859692860000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion adsorbent preparation, and specifically relates to a method for preparing a modified aluminum-based composite lithium adsorbent. Background Art
[0002] With the vigorous development of my country's new energy vehicle industry, the growth rate of my country's lithium salt production is much lower than the growth rate of battery shipments. The development of new lithium resource development and resumption projects has become more difficult and the cycle has lengthened. The demand for lithium resources has shown a continuous upward trend. Therefore, it is urgent to develop more lithium resources. From the perspective of lithium resource form, the global lithium resource supply system is divided into two major systems: lithium extraction from ore and lithium extraction from salt lakes. The proportion of lithium resources in salt lake brine is as high as 62.60%. Compared with lithium extraction from ore, lithium extraction from salt lakes not only accounts for a higher proportion, but also has a simpler way of obtaining and a lower cost of lithium extraction. The production of lithium salt using brine as raw material has low energy consumption and low cost, and the overall cost can save 30% to 50%. Therefore, lithium extraction from salt lakes is a more economical way to obtain lithium resources.
[0003] At present, the main technical routes for extracting lithium from salt lakes in China are precipitation, solvent extraction, membrane separation, calcination leaching, salt gradient solar pond, electrochemical method and adsorption. Since my country's salt lake lithium resources are mainly high in magnesium-lithium ratio, precipitation and solar pond methods are not applicable. Adsorption technology has the advantages of simple process, low cost and high adsorption capacity, and has gradually become one of the most promising methods.
[0004] At present, the inorganic ion adsorbents that are widely studied include: layered adsorbents, amorphous hydroxide adsorbents, ion sieve oxide adsorbents, aluminum salt adsorbents, etc. Among them, aluminum salt adsorbents have good selectivity, large adsorption capacity, and are economical and environmentally friendly, so they have more application prospects.
[0005] CN 102872792A relates to a composite adsorption material for removing lithium ions from natural water bodies and a preparation method thereof. The invention first uses aluminum hydroxide and lithium hydroxide to make aluminum salt, then modifies deep-sea manganese nodules to make lithium ion sieves, then composites the aluminum salt and the lithium subsieve through a colloidal solvent, and finally makes the composite adsorption material through sedimentation, washing, filtering, centrifugation, and air drying. This invention has the characteristics of efficient selective adsorption performance for lithium ions, simple operation, no secondary pollution, low cost and high efficiency. However, the modified aluminum salt adsorbent prepared by the above method still has many disadvantages, such as insufficient adsorption capacity, low cycle stability, and insufficient application range of brine. Therefore, it is necessary to develop a lithium extraction adsorbent with high adsorption capacity, good cycle stability, and wider application range of brine. Summary of the invention
[0006] In order to solve the above-mentioned deficiencies in the prior art, the present invention aims to provide a method for preparing a modified aluminum-based composite lithium adsorbent. The modified aluminum-based composite lithium adsorbent prepared by the method of the present invention has the advantages of high adsorption capacity, good cycle stability, and wide brine application range.
[0007] In order to achieve the above object, the present invention adopts the following technical scheme:
[0008] A method for preparing a modified aluminum-based composite lithium adsorbent comprises the following steps:
[0009] Step S1: dissolving soluble aluminum salt, soluble lithium salt and urea in deionized water, and putting the obtained mixed solution into a hydrothermal reactor for hydrothermal reaction, the hydrothermal reaction temperature is 100-150°C, the reaction time is 3-8h, and after the reaction is completed, filtering and drying to obtain an aluminum adsorbent precursor precipitate; wherein, in the mixed solution, the molar ratio of aluminum to lithium is 0.5-2, and the molar ratio of urea to lithium is 0.5-3; the molar concentration of aluminum in the mixed solution is 1-3mol / L; the soluble aluminum salt is anhydrous aluminum chloride, aluminum chloride hexahydrate, aluminum nitrate, aluminum sulfate, polyaluminum chloride, etc.; the soluble lithium salt is lithium chloride, lithium nitrate, lithium sulfate, lithium hydroxide, etc.; the drying conditions are: drying at 60-100°C for 3-6h; preferably, the hydrothermal reaction temperature is 120-150°C;
[0010] Step S2: soaking the aluminum-based adsorbent precursor precipitate obtained in step S1 in a lithium hydroxide solution; wherein the temperature of the lithium hydroxide solution is 80-120°C, the concentration is 0.5-2 mol / L, and the soaking time is 5-8h; the ratio of the amount of lithium in the lithium hydroxide solution to the amount of aluminum in the soluble aluminum salt in step S1 is (1.6-4):4; preferably, the temperature of the lithium hydroxide solution is 100-120°C;
[0011] Step S3: adding a soluble manganese salt to the solution containing the aluminum-based adsorbent precursor precipitate soaked in step S2, and then performing a hydrothermal reaction, the hydrothermal reaction temperature is 120-150°C, the reaction time is 3-8h, filtering and drying after the reaction is completed to obtain an aluminum-based adsorbent precursor with a manganese-based ion sieve grown thereon; wherein the soluble manganese salt includes manganese nitrate, manganese sulfate, manganese chloride, etc.; the molar ratio of manganese in the soluble manganese salt to the lithium hydroxide in step S2 is 1-2; the drying conditions are: drying at 60-100°C for 3-6h; preferably, the hydrothermal reaction temperature is 140-150°C;
[0012] Step S4: adding the aluminum-based adsorbent precursor on which the manganese-based ion sieve is grown obtained in step S3 into an acid for stirring and washing; wherein the acid is hydrochloric acid, nitric acid or sulfuric acid, the acid concentration is 0.5-2 mol / L, the acid washing solid-liquid ratio is 1g:50ml-1g:100ml, and the stirring time is 5-10h;
[0013] Step S5: After the acid washing in step S4, the precipitate is washed with water for 1-3 times, and then dried to obtain a powder adsorbent material, namely the modified aluminum-based composite lithium adsorbent; wherein the drying conditions are: drying at 60-100° C. for 3-6 hours.
[0014] The modified aluminum-based composite lithium adsorbent prepared by the above method is used in lithium extraction from brine.
[0015] Furthermore, the pH of the brine is 7-14, and the lithium ion concentration in the brine is 50-200 ppm.
[0016] Furthermore, the solid-liquid ratio of the modified aluminum-based composite lithium adsorbent to the brine is 1g:500ml.
[0017] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0018] (1) The modified aluminum-based composite lithium adsorbent prepared by the present invention is prepared by hydrothermal reaction of soluble aluminum salt and lithium salt in urea aqueous solution to obtain aluminum-based adsorbent precursor precipitate; then soaking it in a lithium hydroxide solution of a certain temperature and concentration for a certain period of time, adding manganese salt, and hydrothermal reaction to obtain an aluminum-based adsorbent precursor of an in-situ grown manganese-based ion sieve; finally, washing with acid to elute lithium ions, and drying to obtain. The modified aluminum-based composite lithium adsorbent prepared by the method of the present invention has the advantages of high adsorption capacity, good cycle stability, and wide application range of brine.
[0019] (2) The manganese-based ion sieve is grown in situ on the synthesized aluminum-based adsorbent precursor precipitate, and it grows inside and on the surface of the aluminum-based adsorbent precursor precipitate. In addition, to generate the manganese-based ion sieve in situ, the synthesized aluminum-based adsorbent precipitate must first be immersed in a lithium hydroxide solution of a certain temperature and concentration for a certain period of time, and then a manganese salt is added for hydrothermal reaction. Immersing in the lithium hydroxide solution in advance is beneficial to enriching lithium hydroxide inside and on the surface of the aluminum-based adsorbent precursor precipitate, providing more synthesis sites for the in situ formation of the manganese-based ion sieve. After acid washing, the aluminum-based adsorbent precursor of the in situ grown manganese-based ion sieve releases lithium ions to form vacancies, which can selectively adsorb lithium ions in brine, thereby improving the adsorption capacity of the composite lithium adsorbent.
[0020] (3) The in-situ generated manganese ion sieve is also beneficial to the connection and fixation of the aluminum adsorbent precursor, thereby enhancing the adsorption stability of the aluminum-based adsorbent. In terms of adsorption performance, the aluminum adsorbent and the manganese ion sieve work together to greatly increase its adsorption capacity. The manganese ion sieve itself has good adsorption stability. Its in-situ growth in the aluminum-based adsorbent promotes the structural stability of the aluminum-based adsorbent, thereby increasing its cyclic stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The capacity change diagram of the modified aluminum-based composite lithium adsorbent prepared in Example 1-4 during the cyclic adsorption and desorption process in simulated brine, (left) is the cyclic adsorption capacity diagram, and (right) is the cyclic desorption capacity diagram.
[0022] Figure 2 The capacity change diagram of the lithium adsorbent material prepared in Comparative Examples 1-6 during the cyclic adsorption and desorption process in simulated brine, (left) is the cyclic adsorption capacity diagram, and (right) is the cyclic desorption capacity diagram. DETAILED DESCRIPTION
[0023] The applicant further describes the technical solution of the present invention in combination with specific embodiments and drawings below, but the scope of protection requested by the claims of the present invention is not limited to these embodiments.
[0024] In the following embodiments and comparative examples, the simulated brine used is prepared by accurately weighing a certain amount of lithium chloride and dissolving it in 500 ml of deionized water to prepare a solution with a lithium ion concentration of 50-200 ppm, thereby obtaining a simulated brine with a pH of 7; and further adjusting the pH of the simulated brine to ≤14 by adding NaOH solution.
[0025] Embodiment 1 A method for preparing a modified aluminum-based composite lithium adsorbent comprises the following steps:
[0026] (1) 0.1 molAlCl 3 6H 2 O, 0.2 mol LiCl, and 0.1 mol urea were mixed into 100 ml of deionized water, and the resulting mixture was placed in a hydrothermal reactor (200 mL) for hydrothermal reaction at a temperature of 100 ° C. After reacting for 3 h, vacuum filtration was performed and the mixture was dried at 70 ° C for 5 h to obtain an aluminum-based adsorbent precursor precipitate;
[0027] (2) immersing the aluminum-based adsorbent precursor precipitate obtained in step (1) in a lithium hydroxide solution, wherein the temperature of the lithium hydroxide solution is 80° C., the volume is 150 mL, the concentration is 0.5 mol / L, and the immersion time is 5 h;
[0028] (3) adding 0.125 mol of manganese nitrate to the solution containing the aluminum-based adsorbent precursor precipitate soaked in step (2), followed by a hydrothermal reaction at a temperature of 120° C. for 3 h, followed by vacuum filtration and drying at 70° C. for 5 h to obtain an aluminum-based adsorbent precursor having grown a manganese-based ion sieve;
[0029] (4) The aluminum-based adsorbent precursor on which the manganese-based ion sieve is grown obtained in step (3) is placed in 200 mL of 0.5 mol / L dilute hydrochloric acid at a solid-liquid ratio of 1 g:50 ml, and acid-washed with stirring at a constant temperature for 5 h;
[0030] (5) After acid washing, the precipitate is washed with water twice, and then dried at 70° C. for 5 h to obtain a powder adsorbent material, namely the modified aluminum-based composite lithium adsorbent.
[0031] This embodiment also includes the application of the aluminum-based composite lithium adsorbent prepared by the preparation method, and the specific steps are:
[0032] (1) Adsorption: 1g of dried powdered adsorbent was placed in 500ml of simulated brine with pH=7 (the lithium ion concentration in the brine was 50ppm) for adsorption, with a solid-liquid ratio of 1g:500ml, and adsorption was carried out at 25°C for 2h. After the adsorption was completed, the adsorbent and the filtrate were filtered to separate, the lithium ion concentration in the filtrate was tested, and the adsorption capacity was calculated. The adsorption capacity calculation formula is as follows:
[0033]
[0034] Q 1 is the amount of lithium (Li) adsorbed by a unit mass of adsorbent when the adsorption reaches equilibrium, mg / g; C 0 is the initial concentration of lithium (Li) in the solution, mg / L; C i is the residual concentration of lithium (Li) in the solution when the adsorption reaches equilibrium, mg / L; V is the volume of the solution during the adsorption reaction, L; m is the dosage of the adsorbent, g.
[0035] (2) Desorption: The adsorbent after adsorption is placed in 0.01 mol / L dilute hydrochloric acid for stirring and pickling. The desorption solid-liquid ratio is 1g:100ml. After desorption at 25℃ for 2h, filter, separate the adsorbent and the filtrate, test the lithium ion concentration in the filtrate, and calculate the desorption capacity. The filter residue can be recycled after drying at 70℃ for 5h. The desorption capacity calculation formula is as follows:
[0036]
[0037] Q 2 is the amount of lithium (Li) adsorbed by the adsorbent per unit mass when the desorption reaches equilibrium, mg / g; C i is the final concentration of lithium (Li) in the desorption solution, mg / L; C 0 is the lithium (Li) concentration in the initial desorption solution, mg / L; V is the volume of the solution during the desorption reaction, L; m is the dosage of the adsorbent, g.
[0038] (3) Recyclability: The desorbed adsorbent is filtered and dried, and then re-adsorbed. The adsorption solid-liquid ratio is 1g:500ml, and the desorption solid-liquid ratio is 1g:100ml. Repeat the cycle until the adsorption capacity decreases significantly and the cycle is stopped. The number of cycles is recorded.
[0039] Embodiment 2 A method for preparing a modified aluminum-based composite lithium adsorbent comprises the following steps:
[0040] (1) 0.1 molAlCl 3 6H 2 O, 0.1 mol LiCl, and 0.1 mol urea were mixed into 100 ml of deionized water, and the resulting mixture was placed in a hydrothermal reactor (200 mL) for hydrothermal reaction at a temperature of 110 ° C. After reacting for 5 h, vacuum filtration was performed and the mixture was dried at 70 ° C for 5 h to obtain an aluminum-based adsorbent precursor precipitate;
[0041] (2) immersing the aluminum-based adsorbent precursor precipitate obtained in step (1) in a lithium hydroxide solution, wherein the temperature of the lithium hydroxide solution is 90° C., the volume is 100 mL, the concentration is 1 mol / L, and the immersion time is 6 h;
[0042] (3) adding 0.1 mol of manganese sulfate to the solution containing the aluminum-based adsorbent precursor precipitate soaked in step (2), followed by a hydrothermal reaction at a temperature of 130° C. for 5 h, followed by vacuum filtration and drying at 70° C. for 5 h to obtain an aluminum-based adsorbent precursor having grown a manganese-based ion sieve;
[0043] (4) The aluminum-based adsorbent precursor on which the manganese-based ion sieve is grown obtained in step (3) is placed in 280 mL of 1 mol / L dilute nitric acid at a solid-liquid ratio of 1 g:70 ml, and acid-washed with stirring at a constant temperature for 7 h;
[0044] (5) After acid washing, the precipitate is washed with water twice, and then dried at 70° C. for 5 h to obtain a powder adsorbent material, namely the modified aluminum-based composite lithium adsorbent.
[0045] The present embodiment also includes the application of the aluminum-based composite lithium adsorbent prepared by the preparation method. The specific adsorption, desorption and recycling steps are the same as those in Example 1. The difference is that the simulated brine of the object to be treated in this embodiment is different and the concentration of the dilute hydrochloric acid used in the desorption step is different. The simulated brine in this embodiment is: simulated brine with pH = 9 (the lithium ion concentration in the brine is 80 ppm); the concentration of the dilute hydrochloric acid used in the desorption step of this embodiment is 0.03 mol / L.
[0046] Embodiment 3 A method for preparing a modified aluminum-based composite lithium adsorbent comprises the following steps:
[0047] (1) 0.3 molAlCl 3 6H 2 O, 0.2 mol LiCl, and 0.4 mol urea were mixed into 100 ml of deionized water, and the resulting mixture was placed in a hydrothermal reactor (200 mL) for hydrothermal reaction at a temperature of 120°C. After reacting for 7 hours, vacuum filtration was performed and the mixture was dried at 70°C for 5 hours to obtain an aluminum-based adsorbent precursor precipitate;
[0048] (2) immersing the aluminum-based adsorbent precursor precipitate obtained in step (1) in a lithium hydroxide solution, wherein the temperature of the lithium hydroxide solution is 100° C., the volume is 80 mL, the concentration is 1.5 mol / L, and the immersion time is 7 h;
[0049] (3) adding 0.24 mol of manganese chloride to the solution containing the aluminum-based adsorbent precursor precipitate soaked in step (2), followed by a hydrothermal reaction at a temperature of 140° C. for 7 h, followed by vacuum filtration and drying at 70° C. for 5 h to obtain an aluminum-based adsorbent precursor having grown a manganese-based ion sieve;
[0050] (4) The aluminum-based adsorbent precursor on which the manganese-based ion sieve is grown obtained in step (3) is placed in 280 mL of 1.5 mol / L sulfuric acid at a solid-liquid ratio of 1 g:70 ml, and acid-washed with stirring at a constant temperature for 9 h;
[0051] (5) After acid washing, the precipitate is washed with water twice, and then dried at 70° C. for 5 h to obtain a powder adsorbent material, namely the modified aluminum-based composite lithium adsorbent.
[0052] The present embodiment also includes the application of the aluminum-based composite lithium adsorbent prepared by the preparation method. The specific adsorption, desorption and recycling steps are the same as those in Example 1. The difference is that the simulated brine of the object to be treated in this embodiment is different and the concentration of the dilute hydrochloric acid used in the desorption step is different. The simulated brine in this embodiment is: simulated brine with pH = 11 (the lithium ion concentration in the brine is 150 ppm); the concentration of the dilute hydrochloric acid used in the desorption step of this embodiment is 0.05 mol / L.
[0053] Embodiment 4 A method for preparing a modified aluminum-based composite lithium adsorbent comprises the following steps:
[0054] (1) 0.2 molAlCl 3 6H 2O, 0.1 mol LiCl, and 0.3 mol urea were mixed into 100 ml of deionized water, and the resulting mixture was placed in a hydrothermal reactor (200 mL) for hydrothermal reaction at a temperature of 150 ° C. After reacting for 8 h, vacuum filtration was performed and the mixture was dried at 70 ° C for 5 h to obtain an aluminum-based adsorbent precursor precipitate;
[0055] (2) immersing the aluminum-based adsorbent precursor precipitate obtained in step (1) in a lithium hydroxide solution, wherein the temperature of the lithium hydroxide solution is 120° C., the volume is 50 mL, the concentration is 2 mol / L, and the immersion time is 8 h;
[0056] (3) adding 0.2 mol of manganese carbonate to the solution containing the aluminum-based adsorbent precursor precipitate soaked in step (2), followed by a hydrothermal reaction at a temperature of 150° C. for 8 h, followed by vacuum filtration and drying at 70° C. for 5 h to obtain an aluminum-based adsorbent precursor having grown a manganese-based ion sieve;
[0057] (4) The aluminum-based adsorbent precursor on which the manganese-based ion sieve is grown obtained in step (3) is placed in 360 mL of 2 mol / L sulfuric acid at a solid-liquid ratio of 1 g:90 ml, and acid-washed with stirring at a constant temperature for 10 h;
[0058] (5) After acid washing, the precipitate is washed with water twice, and then dried at 70° C. for 5 h to obtain a powder adsorbent material, namely the modified aluminum-based composite lithium adsorbent.
[0059] The present embodiment also includes the application of the aluminum-based composite lithium adsorbent prepared by the preparation method. The specific adsorption, desorption and recycling steps are the same as those in Example 1. The difference is that the simulated brine of the object to be treated in this embodiment is different and the concentration of the dilute hydrochloric acid used in the desorption step is different. The simulated brine in this embodiment is: simulated brine with pH = 14 (the lithium ion concentration in the brine is 200 ppm); the concentration of the dilute hydrochloric acid used in the desorption step of this embodiment is 0.08 mol / L.
[0060] Comparative Example 1 Preparation method of an aluminum-based adsorbent
[0061] Compared with Example 1, this comparative example does not grow the manganese ion sieve in situ, that is, steps (2) to (3) are not performed. The specific steps are as follows:
[0062] (1) 0.1 molAlCl 3 6H 2 O, 0.2 mol LiCl, and 0.1 mol urea were mixed into 100 ml of deionized water, and the resulting mixture was placed in a hydrothermal reactor (200 mL) for hydrothermal reaction at a temperature of 100 ° C. After reacting for 3 h, vacuum filtration was performed and the mixture was dried at 70 ° C for 5 h to obtain an aluminum-based adsorbent precursor precipitate;
[0063] (2) The aluminum-based adsorbent precursor precipitate obtained in step (1) was placed in 200 mL of 0.5 mol / L dilute hydrochloric acid at a solid-liquid ratio of 1 g:50 ml, and acid washed with constant temperature stirring for 5 h;
[0064] (3) After acid washing, the precipitate is washed with water twice, and then dried at 70° C. for 5 h to obtain a powder adsorbent material, namely the aluminum-based adsorbent.
[0065] This comparative example also includes the application of the aluminum-based adsorbent prepared by the preparation method, and the specific adsorption, desorption and recycling steps are exactly the same as those in Example 1.
[0066] Comparative Example 2 Preparation method of a modified aluminum-based composite lithium adsorbent
[0067] Compared with Example 1, in this comparative example, the in-situ grown manganese ion sieve was prepared without being immersed in a lithium hydroxide solution in advance, that is, step (2) was not performed. The specific steps are:
[0068] (1) 0.1 molAlCl 3 6H 2 O, 0.2 mol LiCl, and 0.1 mol urea were mixed into 100 ml of deionized water, and the resulting mixture was placed in a hydrothermal reactor (200 mL) for hydrothermal reaction at a temperature of 100 ° C. After reacting for 3 h, vacuum filtration was performed and the mixture was dried at 70 ° C for 5 h to obtain an aluminum-based adsorbent precursor precipitate;
[0069] (2) adding the aluminum-based adsorbent precursor precipitate obtained in step (1) and 0.125 mol of manganese nitrate to a 150 mL lithium hydroxide solution with a concentration of 0.5 mol / L, followed by a hydrothermal reaction at a temperature of 120° C. for 3 h, followed by vacuum filtration and drying at 70° C. for 5 h to obtain an aluminum-based adsorbent precursor composited with a manganese-based ion sieve;
[0070] (3) The aluminum-based adsorbent precursor composited with the manganese-based ion sieve obtained in step (2) was placed in 200 mL of 0.5 mol / L dilute hydrochloric acid at a solid-liquid ratio of 1 g:50 ml, and acid washed with stirring at a constant temperature for 5 h;
[0071] (4) After acid washing, the precipitate is washed with water twice, and then dried at 70° C. for 5 h to obtain a powder adsorbent material, namely the modified aluminum-based composite lithium adsorbent.
[0072] This comparative example also includes the application of the aluminum-based composite lithium adsorbent prepared by the preparation method, and the specific adsorption, desorption and recycling steps are exactly the same as those in Example 1.
[0073] Comparative Example 3: A method for preparing a manganese ion sieve
[0074] In this comparative example, compared with Example 1, the manganese ion sieve is directly prepared by hydrothermal method, and the specific steps are as follows:
[0075] (1) adding 0.125 mol of manganese nitrate to a 150 mL lithium hydroxide solution with a concentration of 0.5 mol / L, and then placing the resulting mixture into a hydrothermal reactor (200 mL) for hydrothermal reaction at a temperature of 120° C. for 3 h, followed by vacuum filtration and drying at 70° C. for 5 h;
[0076] (2) After drying, add 200 mL of 0.5 mol / L dilute hydrochloric acid at a solid-liquid ratio of 1 g:50 ml, and stir at a constant temperature for acid washing for 5 h;
[0077] (3) After acid washing, the mixture was filtered and the precipitate was washed twice with water and then dried at 70° C. for 5 h to obtain a manganese-based ion sieve.
[0078] This comparative example also includes the use of the manganese-based ion sieve prepared by the preparation method as a lithium adsorbent, and the specific adsorption, desorption and recycling steps are exactly the same as those in Example 1.
[0079] Comparative Example 4: Preparation method of a modified aluminum-based composite lithium adsorbent
[0080] The only difference between this comparative example and Example 1 is that when preparing the in-situ grown manganese ion sieve in step (3), the hydrothermal reaction temperature is lower than 120°C. Specifically, step (3) performs a hydrothermal reaction under the following reaction conditions: the hydrothermal reaction temperature is 100°C and the reaction time is 3h.
[0081] This comparative example also includes the application of the aluminum-based composite lithium adsorbent prepared by the preparation method, and the specific adsorption, desorption and recycling steps are exactly the same as those in Example 1.
[0082] Comparative Example 5: Preparation method of a modified aluminum-based composite lithium adsorbent
[0083] In this comparative example, compared with Example 4, an aluminum-based adsorbent and a manganese-based ion sieve are first prepared separately, and then the two are compounded by a hydrothermal reaction, and then dried to obtain the modified aluminum-based composite lithium adsorbent. The specific steps are:
[0084] (1) 0.2 mol AlCl 3 6H 2O, 0.1mol LiCl, and 0.3mol urea were mixed into 100ml deionized water, and the resulting mixture was put into a hydrothermal reactor (200mL) for hydrothermal reaction at a temperature of 150°C. After the reaction for 8h, vacuum filtration was performed and the mixture was dried at 70°C for 5h. Then, 360mL of 2mol / L sulfuric acid was added at a solid-liquid ratio of 1g:90ml, and the mixture was acid washed with constant temperature stirring for 10h. After acid washing, the mixture was filtered, and the precipitate was washed with water twice, and then dried at 70°C for 5h to obtain an aluminum adsorbent.
[0085] (2) adding 0.2 mol of manganese carbonate to a 50 mL lithium hydroxide solution with a concentration of 2 mol / L, followed by a hydrothermal reaction at a temperature of 150° C. for 8 h, followed by vacuum filtration and drying at 70° C. for 5 h, and then adding 360 mL of 2 mol / L sulfuric acid at a solid-liquid ratio of 1 g:90 ml, stirring at a constant temperature for acid washing for 10 h, filtering after acid washing, washing the precipitate with water twice, and then drying at 70° C. for 5 h to obtain a manganese ion sieve;
[0086] (3) mixing the manganese-based ion sieve obtained in step (2) with the aluminum-based adsorbent obtained in step (1), adding 100 ml of deionized water for hydrothermal reaction at a temperature of 150° C. for 8 h; and then vacuum filtering to obtain an aluminum-based adsorbent containing the manganese-based ion sieve after the two are combined;
[0087] (4) After filtering, the precipitate was washed with water twice, and then dried at 70° C. for 5 h to obtain a powder adsorbent material, namely the modified aluminum-based composite lithium adsorbent.
[0088] This comparative example also includes the application of the aluminum-based composite lithium adsorbent prepared by the preparation method, and the specific adsorption, desorption and recycling steps are exactly the same as those in Example 4.
[0089] Comparative Example 6 Preparation method of a modified aluminum-based composite lithium adsorbent
[0090] The only difference between this comparative example and Example 2 is that when the aluminum-based adsorbent precursor precipitate is immersed in the lithium hydroxide solution in step (2), the immersion temperature is different. Specifically, step (2) is: immersing the aluminum-based adsorbent precursor precipitate obtained in step (1) in a lithium hydroxide solution, wherein the temperature of the lithium hydroxide solution is 70°C, the volume is 100 mL, the concentration is 1 mol / L, and the immersion time is 6 h.
[0091] This comparative example also includes the application of the aluminum-based composite lithium adsorbent prepared by the preparation method, and the specific adsorption, desorption and recycling steps are exactly the same as those in Example 2.
[0092] Figure 1The capacity change diagram of the modified aluminum-based composite lithium adsorbent prepared in Example 1-4 during the cyclic adsorption and desorption process in simulated brine, (left) is the cyclic adsorption capacity diagram, and (right) is the cyclic desorption capacity diagram.
[0093] The number of cycles of use of the modified aluminum-based composite lithium adsorbent prepared in Examples 1-4, as well as the adsorption capacity and desorption capacity of the last cycle of adsorption are shown in Table 1.
[0094] Table 1
[0095] Adsorption capacity (mg / g) Desorption capacity (mg / g) Cycle times Example 1 23.1 22.4 20 Example 2 25.2 24.8 24 Example 3 27.6 26.9 34 Example 4 30.4 28.6 40
[0096] Figure 2 The capacity change diagram of the modified aluminum-based composite lithium adsorbent prepared in Comparative Examples 1-6 during the cyclic adsorption and desorption process in simulated brine, (left) is the cyclic adsorption capacity diagram, and (right) is the cyclic desorption capacity diagram.
[0097] The number of cycles of use of the modified aluminum-based composite lithium adsorbents prepared in Comparative Examples 1-6, as well as the adsorption capacity and desorption capacity of the last cycle of adsorption are shown in Table 2.
[0098] Table 2
[0099] Adsorption capacity (mg / g) Desorption capacity (mg / g) Cycle times Comparative Example 1 4.2 3.5 5 Comparative Example 2 15.6 13.4 7 Comparative Example 3 13.4 12.7 12 Comparative Example 4 8.5 5.1 5 Comparative Example 5 16.7 13.9 15 Comparative Example 6 18.5 17.9 11
Claims
1. A method for preparing a modified aluminum-based composite lithium adsorbent, characterized in that: The steps include: Step S1: dissolving soluble aluminum salt, soluble lithium salt and urea in deionized water, and placing the obtained mixed solution into a hydrothermal reactor for hydrothermal reaction, the hydrothermal reaction temperature is 100-150°C, the reaction time is 3-8h, and after the reaction is completed, filtering and drying to obtain an aluminum-based adsorbent precursor precipitate; wherein, in the mixed solution, the molar ratio of aluminum to lithium is 0.5-2, the molar ratio of urea to lithium is 0.5-3, and the molar concentration of aluminum in the mixed solution is 1-3 mol / L; Step S2: soaking the aluminum-based adsorbent precursor precipitate obtained in step S1 in a lithium hydroxide solution; wherein the temperature of the lithium hydroxide solution is 80-120° C., the concentration is 0.5-2 mol / L, and the soaking time is 5-8 hours; the ratio of the amount of lithium in the lithium hydroxide solution to the amount of aluminum in the soluble aluminum salt in step S1 is (1.6-4):4; Step S3: adding a soluble manganese salt to the solution containing the aluminum-based adsorbent precursor precipitate soaked in step S2, and then performing a hydrothermal reaction at a temperature of 120-150° C. for a reaction time of 3-8 hours. After the reaction is completed, filtering and drying are performed to obtain an aluminum-based adsorbent precursor having grown a manganese-based ion sieve; wherein the molar ratio of manganese in the soluble manganese salt to lithium hydroxide in step S2 is 1-2; Step S4: adding the aluminum-based adsorbent precursor on which the manganese-based ion sieve is grown obtained in step S3 into acid for stirring and washing; wherein the acid concentration is 0.5-2 mol / L, the acid washing solid-liquid ratio is 1 g:50 ml-1 g:100 ml, and the stirring time is 5-10 h; Step S5: After the acid washing in step S4, the precipitate is washed with water for 1-3 times, and then dried to obtain a powder material, namely the modified aluminum-based composite lithium adsorbent.
2. The method for preparing the modified aluminum-based composite lithium adsorbent according to claim 1, characterized in that: In step S1, the soluble aluminum salt is selected from at least one of anhydrous aluminum chloride, aluminum chloride hexahydrate, aluminum nitrate, aluminum sulfate, and polyaluminum chloride; the soluble lithium salt is selected from at least one of lithium chloride, lithium nitrate, lithium sulfate, and lithium hydroxide; and / or In step S3, the soluble manganese salt is selected from at least one of manganese nitrate, manganese sulfate and manganese chloride.
3. The method for preparing the modified aluminum-based composite lithium adsorbent according to claim 1, characterized in that: In step S1, the hydrothermal reaction temperature is 120-150°C; and / or In step S2, the temperature of the lithium hydroxide solution is 100-120° C.; and / or In step S3, the hydrothermal reaction temperature is 140-150°C.
4. The method for preparing the modified aluminum-based composite lithium adsorbent according to claim 1, characterized in that: In step S4, the acid is hydrochloric acid, nitric acid or sulfuric acid.
5. The method for preparing the modified aluminum-based composite lithium adsorbent according to claim 1, characterized in that: Drying conditions: drying at 60-100°C for 3-6h.
6. Use of the modified aluminum-based composite lithium adsorbent prepared by any method of claims 1-5 in lithium extraction from brine.
7. The use according to claim 6, characterized in that: The pH of the brine is 7-14, and / or the lithium ion concentration in the brine is 50-200 ppm.
8. The use according to claim 6, characterized in that: The solid-liquid ratio of the modified aluminum-based composite lithium adsorbent to the brine is 1g:500ml.
Citation Information
Patent Citations
Composite adsorbing material for removing lithium ions in natural water and preparation method thereof
CN102872792A
Method for regulating and controlling stability of lithium ion sieve by cation doping
CN103991908A